"As I Was Walking Down the Street, Four Strange Guys Came and Took Me Under the Bridge, Where They All Raped Me": An Interpretative Phenomenological Analysis of the Types of Rape Experienced by Men in South Africa. Issue 6 (December 2019) - Mgolozeli, Siyabulela Eric; Duma, Sinegugu Evidence
Globally, rape is regarded as the most demoralizing type of trauma, and it has negative implications for victims and their families. Although rape affects the community in general, there is a paucity of literature on rape victimization of men. As a result, the types of rape experienced by them are not understood, and thus it is often difficult to develop contextually relevant interventions to prevent male rape and to support male rape victims. The objective of this study was to first determine and then describe, the types of rape experienced by men. An interpretative phenomenological analysis (IPA) qualitative approach was used to collect and analyze data from a purposive sample of 11 participants, using semistructured individual interviews. The findings of the study reveal six themes and related subthemes as six types and related subtypes of rape experienced by men as follows: acquaintance rape, including familial rape; stranger rape; gang rape, including corrective-gang rape, drug-facilitated gang rape, pack-hunting rape, women retributive rape (or women vengeance) for violence experienced from men; homophobic rape; prison rape, including transactional rape and gang initiation rape; and armed rape. The findings reveal the different contexts or settings where men are vulnerable to rape. This highlights the possibilities for the development of context-specific sexual violence prevention interventions for men, which include self-defense training and awareness campaigns specific to rape victimization of men. Furthermore, future studies are recommended to expose this pandemic. Activism is advocated to stop the silence around this public and social health issue.